Gastrointestinal Pathogens in Multi-Infected Individuals: A Cluster Analysis of Interaction - Joy Backhaus; Hagen Frickmann; Ralf Matthias Hagen; Gustavo Concha; Ernst Molitor; Achim Hoerauf; Simone Kann (Microorganisms, 2023)
Indigenous people live in remote areas of Colombia. Multiple infections with bacteria, protozoa and/or helminths are common, as well as colonization in various forms. This study focused on the question of whether and to what extent various pathogens interact with each other. Therefore, a mathematical approach was retrospectively applied to PCR-based data of 244 stool samples, collected in two datasets. A stable cluster solution of the pathogens assessed was determined, and a unique configuration between Blastocystis hominis/Campylobacter spp./Giardia lamblia forming cluster 1 and Dientaemoeba fragilis was verified. A pathogen density-dependent interplay appeared between the B. hominis/Campylobacter spp./G. lamblia cluster, D. fragilis and Ascaris lumbricoides. The applied mathematical approach demonstrated that co-infections with parasites of questionable pathological relevance such as B. hominis and D. fragilis can be of diagnostic relevance due to their ability to promote or repress other pathogens. With the increasing availability of highly sensitive multiplexed molecular diagnostic approaches even in resource-limited settings, where multiple colonization of infection events with enteric pathogens in parallel are common, the importance of interpreting whole pathogen patterns rather than just individual pathogen detection may become more and more relevant.